Comparison of a combined torus tank with a composite isogrid support with existing design solutions - Andrii Diadiuk; Volodymyr Lipovskyi (Challenges and Issues of Modern Science)
The development of spacecraft manufacturing technologies has made it possible to create improved designs. In this article, we study the design elements of the combined torus tank. A review of torus tank structures used in launch vehicles that have completed their missions shows that all of them are made of metal. It should be noted that composite materials have a significant advantage due to their higher specific strength compared to metals. When designing aircraft or launch vehicles, opposing criteria must be met. On one hand, the design must be strong, rigid, and stable, while on the other, it must be as lightweight as possible. The research object is a combined torus shell with composite isogrid reinforcement. The research subject is the determination of the advantages and disadvantages of the proposed combined torus tank structures compared to known design options. The purpose of the study is to determine the parameters of a workable combined torus tank with isogrid composite reinforcement using an engineering method of structural calculation, followed by an assessment of the mass characteristics and a comparison with 'prototype' design variants. These design variants are compared with combined torus tanks that have isogrid composite reinforcement created through longitudinal-transverse winding (LTW). In this construction, the liner ensures the hermeticity of the shell and absorbs some of the meridional and annular forces, while the isogrid composite reinforcement absorbs the remaining forces. In this work, we determine the parameters and weight of the combined tanks under prototype load conditions using the engineering method of calculating the efficient torus tank with isogrid composite reinforcement. Based on the results of the numerical analysis, we concluded that using combined torus tanks with isogrid reinforcement is both expedient and effective compared to metal prototypes.